Conveying trunk orientation information through a wearable tactile interface. (October 2020) - Etzi, Roberta; Gallace, Alberto; Massetti, Gemma; D'Agostino, Marco; Cinquetti, Viola; Ferrise, Francesco; Bordegoni, Monica
Abstract: We present the design and test of a wearable device capable to detect the user's trunk orientation with respect to the gravitational field and to provide tactile stimulation to correct tilted positions. Vibrations are delivered to the shoulders, the frontal and dorsal parts of the trunk, by using the human body as an indicator of the four cardinal directions. The device was experimentally tested in normal gravity conditions by thirty-nine volunteers. The efficacy of tactile cues was investigated in comparison to visual and visuo-tactile cues. The results revealed that, despite the fact that the time needed to complete the task was shorter when people were guided by visual signals, the tactile cues were equally informative and, in some cases, the trunk spatial orientation was even more accurate. Overall, tactile cues were evaluated by users as more intuitive, effective and accurate. Highlights: A wearable tactile interface for trunk orientation was designed and tested. Tactile stimuli effectively guided the users towards the target postures. Tactile stimuli were well-accepted by the users. The presentation of pictures to guide trunk orientation was less effective.